KEBIJAKAN BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA DALAM PENGENDALIAN LAJU PERTUMBUHAN PENDUDUK DI KABUPATEN NABIRE - Angwarmas , Koernelis (SKETSA : Jurnal Ilmu-Ilmu Sosial, 2024)
Controlling population growth rate is an attempt to suppress the human birth rate in order to create a society that is in harmony with the natural capacity. Especially for the Nabire Regency, Nabire population growth each year has increased, with an average growth rate of 1.1%. To suppress the population growth rate, Indonesia enacting Law No. 52 Year 2009 on Population Development and Family Development. Presence of Women Empowerment and Family Planning at national and local levels are expected to control the population growth rate both nationally and locally. This study aims to determine how the policy Women Empowerment and Family Planning Nabire in controlling the rate of population growth in the Nabire Regency. The method used is a qualitative research method with data collection techniques used is the study of documentation, interviews and observation. The results of this study indicate that the policy of Women Empowerment and Family Planning Nabire in controlling the population growth rate is the implementation of the Family Planning (KB). Policy supporting factors, among others: the regulatory system, local regulations and rules mayor of Nabire, the Regional Government commitment to family planning and the Empowerment of Women designated by maketh revitalize family planning programs become part of the Development Plan; Commitment partners who are good enough to support the policy of Family Planning and Women's Empowerment; Community participation in planning programs and the Empowerment of Women in Nabire Regency; and competence of employees adequate apparatus. The efforts undertaken include: Mobilizing and empowering the whole community in the program and the Empowerment of Women; Operasion strengthen human resources; Improving the survival and well-being of the family; Ensure the availability of contraceptives and service program for all participants; Improved access to information and reproductive health services; Granting Extension and IEC to members of the PKK, public and Religion through the container meetings PKK village in Posyandu, as well as a group meeting activities to raise family welfare (Generating), group activities of family resilience (BKB, BKR and BKL) by the extension staff planning in the field of the importance for families to the preservation of family planning; Conducting communication and interpersonal counseling (KIP-Counseling) to the EFA are not family planning through home visits by KB officers (PKB).